2021
DOI: 10.1371/journal.pone.0258724
|View full text |Cite
|
Sign up to set email alerts
|

Risk of heavy metals accumulation in soil and wheat grains with waste water irrigation under different NPK levels in alkaline calcareous soil

Abstract: A field study was conducted on the reuse of wastewater from Mardan city to evaluate its risk of contaminating soil and wheat grains at different NPK levels. Three irrigation sources i.e. waste water (WW), canal water (CW) and alternate waste + canal water (WW+CW) were applied to wheat (cv Atta Habib 2010) grown at 0, 50, 75 and 100% NPK levels of 120:90:60 kg N:P2O5:K2O ha-1 at Palatoo Research Farm, Amir Muhammad Khan Campus, Mardan during 2015.The results showed higher grain and biomass yields in WW irrigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Moreover, our results showed that the application of NPK decreased the uptake of B concentration in the roots and shoots of S. oleracea and the organic acid exudation pattern in the roots of the plants grown under B-contaminated soil (Figure 7). It has been confirmed by other researchers that the biomass of various plants increased with the application of NPK under various conditions (Zafarul-Hye et al, 2020;Mussarat et al, 2021). Similar results were established in another study (Saleem et al, 2021), which reported that the maximum plant growth and biomass of Coriandrum sativum were achieved with the combined use of NPK and gibberellic acid.…”
Section: Discussionsupporting
confidence: 81%
“…Moreover, our results showed that the application of NPK decreased the uptake of B concentration in the roots and shoots of S. oleracea and the organic acid exudation pattern in the roots of the plants grown under B-contaminated soil (Figure 7). It has been confirmed by other researchers that the biomass of various plants increased with the application of NPK under various conditions (Zafarul-Hye et al, 2020;Mussarat et al, 2021). Similar results were established in another study (Saleem et al, 2021), which reported that the maximum plant growth and biomass of Coriandrum sativum were achieved with the combined use of NPK and gibberellic acid.…”
Section: Discussionsupporting
confidence: 81%
“…Applying MWR instead of using each water resource alone decreased insignificantly the Zn, Fe, and Cr contents in the barley grains due to a reduction in salinity of the final water resource, which altered the grain yield, availability of metals in soil solution, and metal uptake by plant. Some studies reported an increase in the Zn, Fe, and Cr contents in the grains of wheat irrigated with a combination of wastewater with groundwater (non‐saline water or slightly saline water) compared with that irrigated with groundwater alone (Batool et al, 2023; Mussarat et al, 2021; Sun et al, 2023). Balkhair et al (2014) concluded that the plants irrigated by mixed groundwater and TW adsorbed lower Pb amounts due to the lower Pb content in groundwater compared with TW.…”
Section: Discussionmentioning
confidence: 99%
“…Sharma et al (2007) reported that soil pH, moisture, and nutrients were factors influencing metal accumulation in the plants. According to Mussarat et al (2021), AI with wastewater and canal water resulted in lower levels of Fe, Zn, Cu, Pb, and Cd in wheat grains compared with irrigation with canal water alone due to higher heavy metal contents in wastewater. The application of AI compared to MWR altered the amounts of heavy metals in the grain, indicating decreased contents of Zn, Fe and Cr and increased contents of Cu, Cd and Pb.…”
Section: Effects Of Iw On Heavy Metal Content In the Grainmentioning
confidence: 99%
See 1 more Smart Citation